Kotikaiho - Deledda, Grazia, 1871-1936; Hahl, Jalmari, 1869-1929 (Salt Lake City, UT : Project Gutenberg, 2025)
"Kotikaiho: Avioliittoromaani" by Grazia Deledda is a novel written in the early 20th century. The story revolves around the main character, Regina, as she embarks on a journey to Rome after marrying Antonio. The narrative captures her hopes, dreams, and the stark realities of her new life in a bustling city. The beginning of the novel introduces us to Regina during her train journey to Rome, filled with excitement and trepidation about her new life. As she gazes out at the landscape, she daydreams about the wonders of Rome, contrasting her childhood memories with her new reality. Upon arrival, she is overwhelmed by the crowd and her new family, feeling out of place and suffocated by their expectations. Regina's mixed feelings of joy and apprehension set the stage for her struggles in adjusting to her marriage and the social dynamics she faces in her new environment, marking the start of her complex journey towards self-identity amidst societal pressures. (This is an automatically generated summary.)
Release date is 2025-01-20
Anna Siren and Tapio Riikonen
Keywords: Italian fiction -- Translations into Finnish; Middle class -- Italy -- Rome -- Fiction